Technological Innovations, Activity Based Costing and Satisfaction - Askarany, Davood; Smith, Malcolm; Yazdifar, Hasan (JABM, 2007)
For past two decades, it has been argued that traditional management accounting practices have failed to cope with the requirements of technological changes in manufacturing practices (Askarany, 2005, 2003; Baines & Langfield-Smith, 2003; Beng, Schoch, & Yap, 1994; Bork & Morgan, 1993; Cavalluzzo & Ittner, 2003; Cooper & Kaplan, 1991;Gosselin, 1997; Hartnett & Lowry, 1994; Kaplan, 1984, 1994; Maiga & Jacobs, 2003; Lefebvre & Lefebvre, 1993). In particular, it has been claimed that traditional management accounting techniques are unable to satisfy the users of such techniques in terms of providing them with timely and detailed information. In response to this issue and to overcome the shortcomings of traditional management accounting techniques, activity based-costing (ABC) was introduced in 1980s. However, despite the claimed benefits of ABC, the level of implementation of ABC is still lower than those of traditional management accounting techniques. Shedding light on this debate, current study first examines the level of association between technological changes in manufacturing practices and the level of implementation of ABC to see whether (or not) implementation of technological changes may lead to the implementation of ABC. Then it tests the level of association between the implementation of ABC and the level of satisfaction of ABCs users to see whether (or not) the adopters of ABC are more satisfied than non-adopters. The findings indicate that the diffusion of ABC is associated with the implementation of technological changes in manufacturing practices. However, the results provide no evidence to support that ABC adopters are more satisfied than non-adopters.